Current development and future perspective of IDH1 inhibitors in cholangiocarcinoma. Issue 1 (19th November 2021) - Adeva, Jorge
Abstract: Background and Aims: Biliary tract cancer (BTC) represents a major public health problem due to its increasing rates of incidence and mortality, especially the intrahepatic cholangiocarcinoma (IHCCA) subtype. First line palliative systemic treatment with cisplatin and gemcitabine has been the unique level IA evidence option until last few years when a deeper understanding of its molecular landscape has unveiled CCA as a very rich targetable disease. This has revolutionised the patient's scenario and has brought new targeted therapies guided by molecular aberrations. Isocitrate dehydrogenase (IDH)1 mutations are the most prevalent targetable alteration in CCA (13% of IHCCA). Ivosidenib has been very recently approved by FDA for IDH1 mutated CCA patients based on a randomised clinical trial (ClarIDHy). Methods: We review evidences related to IDH1 mutations in general oncogenesis focusing on CCA and summarise the present and potential future clinical options for the diagnosis and treatment of IDH1m CCA patients. Results: Although the knowledge of the pathogenesis of IDH mutation is still a work in progress, epigenetic and metabolic dysregulation due to the oncometabolite 2‐hydroxyglutarate (2HG) are key in this process. Blocking mIDH1 with ivosidenib has shown significant and clinical benefit for this subgroup of patients. Primary and secondary resistance mechanisms to IDH inhibitors are now being described leading to the investigation of novel treatments such as more potent IDH inhibitors or other drugs that indirectly targets mIDH, as well as looking for novel biomarkers. Conclusions: Although ivosidenib is already available for treating advanced refractory IDH1 mutated CCA, there is still much space to improve outcomes. Several new treatment and diagnostic options in development could hopefully do it for this important subgroup of patients. Abstract :